Kontestasi Wacana PLTN Thorium Pulau Gelasa: Antara Pembangunan, Kerusakan Ekologi, dan Kesenjangan Sosial - Budi Darmawan (Bahasa Indonesia, 2023)
Abstract For the past twelve years up to the present, various efforts have been made by the government to continue the development of a Nuclear Power Plant (NPP) on Gelasa Island, one of which is to persuade the community through positive discourse in order to gain their support and participation. However, the government's discourse initiatives have not been as smooth as anticipated. There has been a discourse contestation, particularly driven by Walhi Babel, who strongly rejects the plan. The purpose of this study is to analyze discourse, specifically the discourse contestation surrounding the construction of the Thorium-based NPP on Gelasa Island. This study does not intend to examine the actors, but rather to examine the discourses that influence the actors' actions. The study employs a qualitative methodology, with the research design utilizing content analysis techniques. In terms of data, this study follows the discourse analysis approach used by Ardianto, which is also based on the discourse analysis of Laclau and Mouffe. For this study, the data consists of online media news and academic writings regarding the discourse on the construction of the Thorium-based NPP on Gelasa Island, Bangka Tengah Regency.